Media Digital dan Pembentukan Spiritualitas Anak: Analisis YouTube Streaming dalam Pelayanan Sekolah Minggu - Sinta Nurlela (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study examines the use of YouTube Streaming in large-class Sunday School as a medium for children’s faith education at Gereja Kalimantan Evangelis (GKE) Nazaret Palangka Raya. The background of this research is the growing integration of digital media into church education, which brings both opportunities and challenges for children’s spiritual formation. The objective of this study is to describe the implementation of YouTube-based Sunday School and to analyze its benefits and challenges related to children’s participation, understanding of faith, and learning concentration. This research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation involving Sunday School teachers and parents. The findings indicate that YouTube Streaming helps maintain continuity of faith education and enhances children’s interest through audio-visual content. However, children’s participation tends to be passive, their understanding of faith often remains at a cognitive level, and their learning concentration is relatively limited. The study concludes that YouTube Streaming functions effectively as a supportive medium but cannot replace direct interaction and relational aspects essential in children’s faith education